Penggunaan Aplikasi Quizwhizzer dalam Peningkatan Penguasaan Kosakata (Mufradat) Bahasa Arab - Nurhanisa, Nurhanisa; Hasmawati, Hasmawati; Ulum, Fatkhul (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
The limited number of studies on the use of the QuizWhizzer application in Arabic vocabulary learning serves as the background for this research, despite its significant potential to support language skills at the Madrasah Aliyah level. This Classroom Action Research aims to examine the planning, implementation, and outcomes of using the QuizWhizzer application as a learning medium to enhance students’ mastery of Arabic vocabulary. The study was conducted over two cycles, each consisting of two sessions, involving 13 tenth-grade students at MA Syekh Yusuf Sungguminasa. The independent variable in this research is the QuizWhizzer application, while the dependent variable is the mastery of Arabic vocabulary. Data collection techniques included observation for qualitative data and evaluation tests for quantitative data. The results indicate that the lesson planning was carried out systematically, and the implementation successfully improved teacher-student interaction. Students’ evaluation scores increased from an average of 72.69% in the first cycle to 85.00% in the second cycle, representing a 12.31% improvement. These findings demonstrate that the use of QuizWhizzer as a learning medium is effective in helping students achieve the Minimum Competency Criteria and significantly enhancing their mastery of Arabic vocabulary.